2012
DOI: 10.15835/nbha4028044
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Quality and Phytochemical Attributes of Some Apricot (Prunus armeniaca L.) Cultivars as Affected by Genotypes and Seasons

Abstract: This study was conducted over two growing seasons (2010 and 2011) to evaluate effects on fruit quality and phytochemical properties of new Turkish cultivars, hybrid between Irano-Caucasian- and European eco-geographic groups, and some important apricot cultivars in the eastern Mediterranean region of Turkey. Fruit quality characteristics, sensory traits, and phytochemical parameters were investigated. The data showed that considerable variation existed in fruit quality and phytochemical properties of Turkish, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
17
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 35 publications
11
17
1
4
Order By: Relevance
“…Our results showed that TP content in different apricot cultivars varied between 0.45 and 1.10 mg GA g -1 FW: this is in the same value range that Caliskan et al (2012) reported for some Turkish apricot varieties. Akin et al (2008) reported higher phenolic compound content (42.33-81.80 mg GA g -1 DW) in apricot fruit.…”
Section: Antioxidant Parameterssupporting
confidence: 88%
See 1 more Smart Citation
“…Our results showed that TP content in different apricot cultivars varied between 0.45 and 1.10 mg GA g -1 FW: this is in the same value range that Caliskan et al (2012) reported for some Turkish apricot varieties. Akin et al (2008) reported higher phenolic compound content (42.33-81.80 mg GA g -1 DW) in apricot fruit.…”
Section: Antioxidant Parameterssupporting
confidence: 88%
“…Some apricot cultivars have recently been evaluated for their antioxidant profile, suggesting their health-promoting effects in the human diet (Leccese et al, 2010). Antioxidant compounds, such as carotenoids, polyphenols, and vitamin C, have been reported in high amounts in apricot fruit (Drogoudi et al, 2008;Dragovic-Uzelac et al, 2009;Hegedüs et al, 2011;Sochor et al, 2011;Caliskan et al, 2012;Fan et al, 2018;Fratianni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some cultivars of apricot have been evaluated for their antioxidant activity, suggesting their health-promoting effects in the human diet (Leccese et al, 2010). Antioxidant compounds, such as carotenoids, polyphenols, and vitamin C, have been evaluated in high amounts in apricot fruit (Caliskan et al, 2012 andFratianni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…7). In general, fruit species, lower L, C and h° values are associated with darker fruit skin color whereas higher values of these variables consists of fruit skin lighter color [Caliskan et al 2012]. Golden Delicious had the lightest fruits with the high L value (72.27).…”
Section: Resultsmentioning
confidence: 93%